Equity valuation : Activision Blizzard, Inc. - Belo, Fernando Guilherme Mantas Gonçalves (2018)
This dissertation aims to present the investment thesis that provides a fair value for the video games software company Activision Blizzard, Inc. The suggested fair value is then compared with the current share price with the objective to issue a buy, hold or sell recommendation as per January 17, 2018. The first component of this dissertation introduces a review of the relevant literature on equity valuation. Afterwards, the company’s business model and industry dynamics affecting the company are discussed. Next, a practical approach is implemented. The models used are the enterprise-discounted cash flow, economic profit, and the relative valuation. The first two models generate a target price of $73 for the firm’s common stock, implying a 6,2% upside to the current market price, leading to a buy recommendation. The relative valuation model also supports the same recommendation. Furthermore, this resultant output is subject to a sensitivity analysis and different scenarios are assessed. An executive summary with key statistics and drivers of the investment thesis is also provided where the reader can easily understand the view this dissertation defends. Finally, a comparison of the results is made with an equity research report from Morgan Stanley. Albeit the recommendation is in line with Morgan Stanley investment note, the reader is shown the major differences in the valuation assumptions and methodologies for the same company.